Transition model for coronavirus management. (23rd March 2022) - Djogbenou, Antoine; Gourieroux, Christian; Jasiak, Joann; Rilstone, Paul; Bandehali, Maygol
Abstract: This paper examines the individual records of patients treated for COVID‐19 during the early phase of the pandemic in Ontario. We trace out daily transitions of patients through medical care of different intensity and address the right truncation in the database. We also examine the sojourn times and reveal duration dependence in the treatments for COVID‐19. The transition model is used to estimate and forecast the counts of patients treated for COVID‐19 in Ontario, while adjusting for the right truncation and right censoring in the sample. This research is based on the Public Health Ontario (PHO) data set from May 7, 2020. Résumé: Un modèle de transition pour la gestion du cononavirus. Cet article examine les historiques individuels des patients traités pour le COVID‐19 au début de le pandémie en Ontario. Nous traçons les transitions journalières des patients recevant des soins médicaux d'intensités différentes et traitons la troncature à droite dans la base de données. Nous examinons également les temps de séjour et révélons une dépendance à la durée dans les traitements du COVID‐19. Le modèle de transition est utilisé pour estimer et prévoir le nombre de patients traités pour le COVID‐19 en Ontario, tout en tenant compte de la troncature à droite et de la censure à droite dans l'échantillon. Cette recherche est basée sur des données de Santé publique Ontario datant du 7 mai 2020.